2020
DOI: 10.1159/000507819
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Moderators of Internet-Based Interventions in Adults with Subthreshold Depression: An Individual Participant Data Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction: Evidence on effects of Internet-based interventions to treat subthreshold depression (sD) and prevent the onset of major depression (MDD) is inconsistent. Objective: We conducted an individual participant data meta-analysis to determine differences between intervention and control groups (IG, CG) in depressive symptom severity (DSS), treatment response, close to symptom-free status, symptom deterioration and MDD onset as well as moderators of intervention outcomes. Methods: Randomized controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 94 publications
6
52
1
Order By: Relevance
“…However, if no traditional therapy is available, priovi could still offer some psychoeducation and comfort, as it has been demonstrated that internet-based psychoeducation can reduce BPD symptoms and improve social functioning [ 12 ]. Moreover, internet interventions have been shown to be suitable low-threshold interventions, also for patients with a high symptom burden [ 38 ]. Priovi seems to be well suited for cognitive exercises and delivering psychoeducation but cannot meet individual needs or address personal issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, if no traditional therapy is available, priovi could still offer some psychoeducation and comfort, as it has been demonstrated that internet-based psychoeducation can reduce BPD symptoms and improve social functioning [ 12 ]. Moreover, internet interventions have been shown to be suitable low-threshold interventions, also for patients with a high symptom burden [ 38 ]. Priovi seems to be well suited for cognitive exercises and delivering psychoeducation but cannot meet individual needs or address personal issues.…”
Section: Discussionmentioning
confidence: 99%
“…Third (and clinically most relevant), given the high strain and specific needs of youth with CC, it might be that this particular group of patients is not responsive to IMIs to the same extent than other patient populations ( Andersson et al, 2019 ; Bendig et al, 2018 ; Domhardt et al, 2020b ). Additionally, empirical knowledge on moderators, for example in regard to therapist involvement ( Baumeister et al, 2014 ; Domhardt et al, 2020a ; Reyes-Portillo et al, 2014 ), support by parents ( Domhardt et al, 2020b ; Fedele et al, 2017 ) or developmentally-related differences in age groups ( Reins et al, 2020 ; Thabrew et al, 2018 ), is still largely pending, but is central to inform the allocation of individual patients to the most fitting psychological intervention, either delivered face-to-face or via digital technology. Next to these efforts toward precision medicine ( Cohen and DeRubeis, 2018 ) and “ precision digital health ” ( Domhardt et al, accepted ), important future directions for forthcoming research are on how to best improve interventions and maximize treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is important to understand the effect of therapeutic guidance in digital therapies because the specific effect of guidance remains unclear. Some authors argue (Reins et al, 2021) that guided therapies are convenient for severe psychopathologies (e.g. major depression), but may have only a limited effect on the efficacy of subthreshold mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Some reviews found that Internet-based interventions are effective in reducing the incidence of depression and decreasing anxiety symptoms in adolescents and adults (e.g. Etzelmueller et al, 2020;Reins et al, 2021). This is contradicted by other reviews, which found only small effects in preventing depression (e.g.…”
Section: Internet-based Therapymentioning
confidence: 97%